Exploring Integrated Language in Use for Undergraduate English Learners through Wayang Stories - Hermayawati Hermayawati (Ahmad Dahlan Journal of English Studies, 2020)
Teaching integrated English skills has been currently becoming a crucial discussion among the teachers in line with the changing of the view about language use. The problem is, how to deliver it due to the limited time allocation (two Semester Credit Unit) per-week with the large amount of materials content. This paper explores the procedure on delivering the four integrated English skills through Wayang stories as the learning materials by involving 40 undergraduate level of English I learners. The data compiled using in-depth observation and integrated skills tests through the given tasks were analyzed both descriptively and numerically. Result of in-depth observation mainly reveals the WUPPA (watching, understanding, paraphrasing, performing and assessing) procedures and its benefit to teach integrated skills learning conceptually. Wayang stories were utilized to educate learners to love their cultures through acquiring the hidden moral messages embedded in each story. Findings show that WUPPA procedures gained relatively moderate achievements due to most learners attained competent (33%) and very competent level (61%) of their language proficiencies. It was only a small part of them (6%) who achieved the ‘Not yet competent’ level. Finally, this study provides an alternative to teach integrated English skills using wayang stories with WUPPA that do not only enrich teaching materials as it makes the learners enjoyable and insightful but also can be used to embed moral values education.